2012
DOI: 10.1111/j.1365-2230.2011.04212.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the hair of patients with scalp psoriasis using atomic force microscopy

Abstract: The hair shafts of patients with scalp psoriasis exhibited the same macropits seen in their nails. Both lesional and nonlesional hairs had similar changes in morphological structure compared with controls. This supports the generalized nature of psoriasis, with changes in hair structure being analogous to the changes seen in skin and nails.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Kim et al used more sensitive atomic force microscopy (AFM) to study the surface morphology of psoriasisderived hair samples compared to normal hair. These studies [12,13] demonstrated that psoriatic hair had thicker cuticle edges, an overall rougher surface and more surface pitting.…”
Section: Psoriasismentioning
confidence: 99%
“…Kim et al used more sensitive atomic force microscopy (AFM) to study the surface morphology of psoriasisderived hair samples compared to normal hair. These studies [12,13] demonstrated that psoriatic hair had thicker cuticle edges, an overall rougher surface and more surface pitting.…”
Section: Psoriasismentioning
confidence: 99%
“…Scalp psoriasis is associated with significant abnormalities in the HF epithelium and with sebaceous gland atrophy (Figure 1B), 3,[26][27][28][29] and the hair shafts of patients with scalp psoriasis can exhibit the same pits as in their nails (Table 1). 30 There may even be a distinct follicular variant of psoriasis. 1,31,32 Yet, overall, only in a small minority of patients scalp psoriasis leads to marked effluvium or psoriatic alopecia.…”
Section: The Hair Folli Cle-psoria S Is a Xis: Clinic Al And His Topa...mentioning
confidence: 99%
“…Conversely, the length of the anagen phase is extended at the site of some psoriatic lesions. In addition, the hair structure is possibly affected by psoriasis [64, 65]. All these features are conveniently explored using the trichogram method which is minimally invasive, cheap, and rapid.…”
Section: Scalp Psoriasismentioning
confidence: 99%